LANGUAGE PICTURE OF THE WORLD AND ITS REFLECTION IN DICTIONARIES OF DIFFERENT GENRE - Irina Takhirovna Rajabova (European Science Publishing, 2024)
The article considers dictionaries as sources containing the main lexical composition of the language with their interpretation and illustration, allows you to reflect a set of concepts called words, i.e. linguistic picture of the world. Attention is focused on the fact that explanatory dictionaries to the greatest extent reflect the linguistic picture of the world, since the interpretation of the lexical meaning of a word represents the concept and interprets different types of knowledge of the people
Keywords: linguistic picture of the world, lexicography, dictionaries, concept, concept sphere, moral and cultural values of the people.